Effect of alanyl-glutamine on leucine and protein metabolism in endotoxemic rats - Holecek, M; Skopec, F; Skalská, H; Sprongl, L (JPEN. Journal of parenteral and enteral nutrition, 2000)
BACKGROUND: Branched-chain amino acids (BCAA; valine, leucine, and isoleucine) have a regulatory effect on protein metabolism and are the main donor for synthesis of alanine and glutamine in the skeletal muscle. This study was performed to investigate whether exogenous alanine or glutamine would affect leucine and protein metabolism in intact and endotoxemic rats. METHODS: Rats were injected with endotoxin of Salmonella enteritidis or saline. Thirty minutes later, the effects of endotoxemia and L-alanyl-L-glutamine (AG) on leucine and protein metabolism were evaluated using a primed constant infusion of [1-14C]leucine, endotoxin, and AG (200 mg/mL) solution or an infusion of [1-14C]leucine without endotoxin or AG. The specificity of the effect of exogenous alanine and glutamine was evaluated by a single infusion of alanine, glutamine, and glycine in a separate study. RESULTS: Endotoxin treatment induced more negative net protein balance caused mainly by an increase in whole-body proteolysis. Protein synthesis increased in kidneys, colon, and spleen, while a decrease was observed in skeletal muscle. The impressive effects of AG were the decrease in plasma branched-chain amino acid (BCAA) levels, decrease in leucine oxidized fraction, and improvement of protein balance associated with a decrease in whole-body proteolysis. Similar changes in leucine and protein metabolism were induced by infusion of alanine or glutamine but not by infusion of glycine. CONCLUSIONS: IV administration of alanine or glutamine improves protein balance and decreases leucine oxidized fraction in postabsorptive state and in endotoxemia. Decreased proteolysis is the main cause of decreased plasma BCAA levels after AG treatment.
Keywords: dipeptidy; Amino Acids, Branched-Chain; Endotoxemia; proteiny; Dipeptides; Proteins; Glutamine; krysa rodu Rattus; Glycine; Leucine; glycin; zvířata; glutamin; potkani Wistar; endotoxemie; kosterní svaly; Rats, Wistar; Male; Alanine; alanin; Muscle, Skeletal; Infusions, Intravenous; Rats; větvené aminokyseliny; Animals; mužské pohlaví; intravenózní infuze; leucin